Analysis of Entrepreneurial Interest Among Entrepreneurial Student of the 2022 Cohort at Universitas Pembangunan Veteran Jawa Timur - Noor Laila Deviani Faridz; Sulastri Irbayuni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines the influence of self-efficacy and motivation on entrepreneurial interest among students of the Entrepreneurship Study Program, Class of 2022, at Universitas Pembangunan Nasional “Veteran” Jawa Timur. Using a quantitative survey method, data were collected from 53 respondents through questionnaires and analyzed with the Partial Least Square (PLS) approach using SmartPLS software. The findings indicate that self-efficacy significantly enhances students’ entrepreneurial interest. Students with strong confidence in their ability to lead, organize, and manage business activities tend to develop higher entrepreneurial intentions. Likewise, motivation has a positive impact on entrepreneurial interest, where the drive to achieve success and self-fulfillment becomes a major factor influencing students to engage in entrepreneurship. The study emphasizes the need to cultivate self-efficacy and intrinsic motivation as essential components in developing independent, confident, and competitive young entrepreneurs who are ready to create innovative business opportunities and contribute to economic growth.